PEMANFAATAN MEDIA POP UP BOOK DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS 3 DI MADRASAH IBTIDAIYAH - Faizatul Widat; Devi Fitriatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the use of pop up book media in social studies learning to improve the understanding of grade III students at Madrasah Ibtidaiyah Negeri 1 Probolinggo. This study uses a qualitative approach with a descriptive type. The research subjects consisted of grade III students and classroom teachers. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis uses an interactive model that includes data reduction, data presentation, and conclusion drawn. The results of the study show that the use of pop up book media can create a more interesting, interactive, and fun learning atmosphere. Students become more active in the learning process, both in asking questions, answering questions, and discussing. In addition, pop up book media is also able to increase students' understanding of IPAS material because of the presentation of material that is visual and concrete so that it is easier for students to understand. It can be concluded that the use of pop up book media is effective in increasing students' understanding of social studies learning in grade III of Madrasah Ibtidaiyah Negeri 1 Probolinggo. However, this study has limitations so that the results cannot be generalized widely because each educational institution has different characteristics.